Funcionalidad familiar y niveles de glicemia en diabéticos tipo 2 en la ciudad de Loja - Coronel Chamorro, Galo Andrés (2014)
The present study seeks to determine the relation between family functionality and glycemic medical control, in type II mellitus diabetic patients cared in the “Manuel Ygnacio Monteros Hospital- IESS of Loja city”. And to establish the importance of the care inclusion of relatives of type 2 diabetic patients. This is a descriptive, prospective and transversal study, where the population is made up of 346 patients, taking as sample 100 patients from February to July of the year 2013. For the research, was applied the Test family APGAR to assess the family functionality; and it was possible to get data of the values of fasting blood glucose and glycosylated hemoglobin. According to the results, was found that in the sample of 100 patients, 50 persons family belongs to a functional, of whom, the 32 keeps adequate blood glycemic levels, and 18 patients had inadequate glycemic control. In the group with family dysfunctionality 27 persons perceive it like severe dysfunctionality, while 23 perceive it like moderate dysfunctionality. In the glycemic medical control of the patients with family dysfunction, the 62% keeps inappropriate blood glycemic levels. Applying the ODDS RATIO was determined that the patients group with family dysfunction, has main predisposition (2.9), for having inappropriate blood glycemic levels. In addition it was possible to know that the population most affected with DMTII is the active paid workers, demonstrating the influence it may have on this population, affecting their life quality. Key words: Family functioning, family dysfunction, blood glucose levels, type II mellitus diabetic.